Monographs on invasive plants in Europe N° 5: Ambrosia trifida L. Issue 2 (3rd April 2021) - Chauvel, Bruno; Fried, Guillaume; Follak, Swen; Chapman, Daniel; Kulakova, Yuliana; Le Bourgeois, Thomas; Marisavljevic, Dragana; Monty, Arnaud; Rossi, Jean-Pierre; Starfinger, Uwe; Tanner, Rob; Tassus, Xavier; et al.
ABSTRACT: Ambrosia trifida L. (giant ragweed, Asteraceae) is native to the North American continent and was introduced into Europe and Asia at the end of the 19 th century. In its native range, this tall annual species is common in riparian and ruderal habitats and is also a major weed in annual cropping systems. For nearly a century, A. trifida has also been of great concern in the U.S. for its highly allergenic pollen, necessitating targeted control measures to reduce its impact on human populations. Based on the distribution of A. trifida in North America and in its introduced range, riparian systems in the rest of the world may be particularly at risk to invasion, with potential negative consequences for their biodiversity. Currently, A. trifida has invaded Asia more widely than Europe, likely due to the more favourable local conditions in Asia. Throughout its introduced range, A. trifida is host to a limited number of invertebrates and pathogens and only a few biological agents are available for its control. The main impacts of A. trifida at a global level are on crop yield and human health, resulting in significant socio-economic impacts. The success of A. trifida invasion in areas in which it has been introduced is still unclear, but climate change may increase climate suitability, increasing the potential for A. trifida to spread. While effective management in cultivated fields seems potentially possible, the development and control of A. trifida in natural riparian habitats is of great concern due to the difficulty of management in these areas.